3D object recognition: Views, moment invariants & perceptron networks - Mohd Yusof, Mashor, Prof. Dr.; M. K., Osman; R., Arshad (Universiti Malaysia Perlis (UniMAP), 2010)
Computer vision recognition typically involves sensors, a model database containing information about the object representations and decision making or categorization. Sensors gather images that are processed to represent it as the database models and a recognition algorithm is applied to find the model to which the object best matches, known as model-based object recognition system.